2014
DOI: 10.1140/epjc/s10052-014-2874-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the $$Z_c(4020)$$ Z c ( 4020 ) , $$Z_c(4025)$$ Z c ( 4025 ) , $$Y(4360)$$ Y ( 4360 ) , and $$Y(4660)$$ Y ( 4660 ) as vector tetraquark states with QCD sum rules

Abstract: In this article, we distinguish the charge conjugations of the interpolating currents, calculate the contributions of the vacuum condensates up to dimension-10 in the operator product expansion, and we study the masses and pole residues of the J PC = 1 −± hidden charmed tetraquark states with the QCD sum rules. We suggest a formulawith the effective mass M c = 1.8 GeV to estimate the energy scales of the QCD spectral densities of the hidden charmed tetraquark states, which works very well. The numerical result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
190
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(193 citation statements)
references
References 76 publications
3
190
0
Order By: Relevance
“…Following this work, many studies have synthesized black TiO 2 through various methods. [60][61][62][63][64] However, some of the as-obtained black TiO 2 materials fail in visible light-driven photocatalysis, although the dramatic enhancement in light absorption is achieved. [61,64] We believe that the key factor is the balance between the light absorption enhanced by defects and the defect-induced carrier traps.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…Following this work, many studies have synthesized black TiO 2 through various methods. [60][61][62][63][64] However, some of the as-obtained black TiO 2 materials fail in visible light-driven photocatalysis, although the dramatic enhancement in light absorption is achieved. [61,64] We believe that the key factor is the balance between the light absorption enhanced by defects and the defect-induced carrier traps.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…[18][19][20] The light absorption range of semiconductor materials can be enhanced or expanded by introducing oxygen vacancies, which results in the extended light absorption spectra and band gap narrowing. 18,21 Recently, oxygen-vacancy associated properties have been widely surveyed in simple semiconductors, such as TiO 2 , [18][19][20]22 Fe 2 O 3 , 23 and ZnO. [24][25][26] However, to the best of our knowledge, the oxygen vacancies in La(OH) 3 and their influence on the band structure and photocatalytic activity have seldom been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].Based on constrained triaxial covariant density functional theory (CDFT) calculations, it has been suggested that multiple chiral doublet (MχD) bands can exist in a single nucleus [21][22][23][24][25][26]. The theoretical prediction of MχD bands stimulated lots of experimental efforts [27][28][29][30][31].…”
mentioning
confidence: 99%
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%